Unraveling the Potassium Storage Mechanism in Graphite Foam. Issue 22 (8th April 2019) - Liu, Jilei; Yin, Tingting; Tian, Bingbing; Zhang, Bowei; Qian, Cheng; Wang, Zhiqiang; Zhang, Lili; Liang, Pei; Chen, Zhen; Yan, Jiaxu; Fan, Xiaofeng; Lin, Jianyi; et al.
Abstract: Potassium‐intercalated graphite intercalation compounds (K‐GICs) are of particular physical and chemical interest due to their versatile structures and fascinating properties. Fundamental insights into the K + storage mechanism, and the complex kinetics/thermodynamics that control the reactions and structural rearrangements allow manipulating K‐GICs with desired functionalities. Here operando studies including in situ Raman mapping and in situ X‐ray diffraction (XRD) characterizations, in combination with density‐functional theory simulations are carried out to correlate the real‐time electrochemical K + intercalation/deintercalation process with structure/component evolution. The experimental results, together with theoretical calculations, reveal the reversible K‐GICs staging transition: C ↔ stage 5 (KC60 ) ↔ stage 4 (KC48 ) ↔ stage 3 (KC36 ) ↔ stage 2 (KC24 /KC16 ) ↔ stage 1 (KC8 ). Moreover, the staging transition is clearly visualized and an intermediate phase of stage 2 with the stoichiometric formula of KC16 is identified. The staging transition mechanism involving both intrastage transition from KC24 (stage 2) to KC16 (stage 2) and interstage transition is proposed. The present study promotes better fundamental understanding of K + storage behavior in graphite, develops a nondestructive technological basis for accurately capture nonuniformity in electrode phase evolution across the length scale of graphite domains, and offers guidance for efficient research in other GICs. Abstract : Operando techniques including Raman mapping and X‐ray diffraction (XRD), in combination with theoretical simulations, have enabled the direct visualization of potassium‐intercalated graphite intercalation compounds staging evolution precisely during electrochemical operations, with high temporal and spatial resolution. Moreover, solid evidence for a new stoichiometric formula of KC16 and intrastage transition within stage 2 are found.